Tyrosine phosphorylation patterns and size modification of the Helicobacter pylori CagA protein after translocation into gastric epithelial cells. - Backert, Steffen; Müller, E.C.; Jungblut, P.R.; Meyer, Thomas F. (Proteomics, 2001)
Helicobacter pylori is one of the most common bacterial pathogens that causes a variety of gastric diseases. During infection, the immuno-dominant H. pylori CagA protein is translocated and tyrosine-phosphorylated in gastric epithelial cells. We compared tyrosine phosphorylation patterns of five CagA variants by two-dimensional electrophoresis (2-DE) and immunoblotting studies. Tyrosine-phosphorylated CagA was detected as two distinct protein species in strains P12, P227, G27 and 26695 suggesting that two tyrosine residues of CagA can be phosphorylated both separately and simultaneously. Prediction programs revealed the presence of three putative tyrosine phosphorylation motifs in the sequences of CagA. Mutations in these motifs were identified suggesting that only two putative phosphorylation-relevant tyrosines are present in each CagA variant. CagA of strain J99 was found to be unique because essential codons were mutated in each of the three motifs and, consequently, revealed no tyrosine phosphorylation signals at all. These findings support the view that CagA from different H. pylori strains can be tyrosine-phosphorylated at one or two out of three predicted positions. Additionally, truncated CagA protein species of about 100-105 kDa (p100CagA) have been detected after infection with some of the H. pylori strains. The isoelectric point determined by both 2-DE and sequence analysis suggested that p100CagA represents the amino (N)-terminal part of the protein. Translocation, tyrosine phosphorylation and size modification of CagA might be involved in host signal transduction and development of gastric disease.